2012
DOI: 10.1002/tee.21725
|View full text |Cite
|
Sign up to set email alerts
|

Lightning occurrence characteristics in Japan for 17 years: observation results with lightning location systems of electric power utilities from 1992 to 2008

Abstract: We summarize the lightning data for 17 years from 1992 to 2008 obtained with lightning location systems of nine electric power utilities in Japan and analyze them. The observed annual number of lightning flashes of which the current is more than 10 kA is 400 000–800 000 and the 50% value of the cumulative distribution of lightning peak currents is about 23 kA in recent times. The variation of lightning occurrence characteristics by areas, seasons, and so on, is clarified. Comparison of the obtained data with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…In winter, on the contrary, most of lightning occurs in the coastal area of the Sea of Japan. These occurrence patterns are same as reported previously .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In winter, on the contrary, most of lightning occurs in the coastal area of the Sea of Japan. These occurrence patterns are same as reported previously .…”
Section: Resultssupporting
confidence: 91%
“…As stated before, the lightning location systems of electric power utilities in Japan have been replaced by new versions. It has been shown that the number of observed lightning strikes is increasing as detected by the newer versions of the lightning location systems . In order to understand the long‐term trend of lightning occurrence, we analyzed the annual variation of thunderstorm days whose effect on the upgraded system is considered to be relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in many regions of the world, lightning is one of the causes of natural disaster in Japan. Lightning is most frequent in summer, especially in the inland region (Japan Meteorological Agency, 1968;Shindo et al, 2012;Ishii et al, 2014), where daytime heating enhances thermal instability causing the development of convective clouds. Lightning also occurs in winter on the northwestern coast of Honshu under an outbreak of cold air that is heated and moistened over the Sea of Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Based on JMA lightning data since the 1960s, the decadal variation in lightning frequency has been investigated (e.g., Kitagawa 1989;Yoshida 2002). Some researchers have prepared maps of the climatological frequency of lightning over the Japanese archipelago based on radio waves emitted by lightning strokes, and have examined its seasonal variation (e.g., Shindo et al 2012). Saito et al (2012) reported on the seasonal variation of high-current lightning discharges; however, these data were limited to land and therefore, it was impossible to describe the features of lightning over the open ocean.…”
Section: Introductionmentioning
confidence: 99%